The Comparison of Widal Slide Examination Results between Tubex TF on Febrile Observation Patients Over 3 Days - Nosa Ika Cahyariza; Rofiatu Sholihah (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2019)
Typhoid fever is systematic bacterial disease usually occurs and has a high mortality rate each year, a disease transmitted from person to person due to contamination of feces, food, and water. The cause is bacterium Salmonella enterica serovar Typhi (S. Typhi) which is a natural host and reservoir for human. The limitations of the diagnostic test led to the increasing mortality rate due to typhoid fever. Besides ensuring infection in individuals, accurate serological tests are needed to ascertain the actual burden of the disease. Serological tests which are usually carried out in Puskesmas and hospital are Widal and Tubex Tf examinations. This study aims to determine whether there are differences in Widal and Tubex TF serological examinations in febrile patients over three days non-typhoid so patients can immediately find out whether they have typhoid fever or not. This study used a laboratory exploration method by examining 24 samples using Widal TYDAL and TUBEX® TF IDL Biotech. As many as 24 samples were examined by widal with antisera O, H, AH, and BH. Twenty-four of the same samples analyzed by TUBEX® TF. Results comparison of diagnostic from both methods will be compared using Mc Nemar test with significance = 0.05. Based on the examination which had done, it showed the difference in the results of Widal slide and lg M Anti Salmonella (Tubex Tf) in patients with febrile observation over three days. So, it can conclude that Tubex Tf examinations were better that widal slide examination because Tubex Tf uses Salmonella typhi anti-O9 antigen which can distinguish these organisms from >99% other Salmonella bacteria serotypes so that Tubex Tf examination is more specific.